1980
DOI: 10.3382/ps.0591211
|View full text |Cite
|
Sign up to set email alerts
|

Control of Northern Fowl Mite with Permethrin and Fenvalerate, Two Synthetic Pyrethroid Compounds

Abstract: Trials were conducted to evaluate the efficacy of permethrin and fenvalerate, two synthetic pyrethroid compounds, for the control of the northern fowl mite, Ornithonyssus sylviarum (Canestrini and Fanzago), on White Leghorn hens. Fenvalerate at .0125%, .025%, and .05% active ingredient (ai) were as effective as carbaryl at .5% ai for 56 days posttreatment. Permethrin at .01%, .025%, and .05% ai were as effective, or better than, malathion at .27% ai for 56 days posttreatment. All treatments were applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Loomis and Dunning (1980) used rates of 29.5, 44, and 74 ml per bird with 30 psi and obtained 95% mite control for 49 days beginning 1 day after treatment, 100% control after 2 weeks, and 100%o control for 91 days after 1 week, respectively. Williams and Berry (1980) applied 40 ml of finished spray per bird at 60 psi and had 100% control for 56 days. Similar control was also obtained with .01% and .025% sprays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loomis and Dunning (1980) used rates of 29.5, 44, and 74 ml per bird with 30 psi and obtained 95% mite control for 49 days beginning 1 day after treatment, 100% control after 2 weeks, and 100%o control for 91 days after 1 week, respectively. Williams and Berry (1980) applied 40 ml of finished spray per bird at 60 psi and had 100% control for 56 days. Similar control was also obtained with .01% and .025% sprays.…”
Section: Resultsmentioning
confidence: 99%
“…To date, under laboratory and limited field tests, the synthetic pyrethroids have been reported to be extremely effective against the northern fowl mite: Ectiban® (permethrin) (Hall et al, 1978;Lancaster and Simco, 1980;Loomis and Dunning, 1980), Atroban® (permethrin) (Loomis and Dunning, 1980;Williams and Berry, 1980) and Ectrin® (fenvalerate) (Hall et al, 1978;Combs, 1978;Loomis et al, 1979;Williams and Berry, 1980). Chlordimeform was also found effective for northern fowl mite control but has never been registered for use (Hall et al, 1975;Christensen et al, 1977).…”
Section: Introductionmentioning
confidence: 93%
“…After 28 days, birds were mitefree in treatments of .05% EC spray and .25% dust. Hall et al (1978), Loomis et al (1979), and Williams and Berry (1980) all suggested that the synthetic pyrethroids will play an important role in further NFM control for the poultry industry.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, considerable interest has been shown in the potential of synthetic pyrethroid acaricides for northern fowl mite control. Demonstrating high acute toxicity to these mites, acceptable residual activity, low requisite concentrations, and a low order of acute toxicity to poultry, fenvalerate and permethrin appear to be wellsuited for this use (Hall et al, 1978;Loomis et al, 1979;Lancaster and Simco, 1980;Loomis and Dunning, 1980;Williams and Berry, 1980;Collison et al, 1981;Arthur and Axtell, 1982). Application techniques evaluated included high or low pressure sprays and dust treatments.…”
Section: Introductionmentioning
confidence: 97%